Experimental Study on the System Performance of Adjacent Precast Concrete Box Beam Bridges. (13th March 2020) - Leng, Yanling; Zhang, Jinquan; Jiang, Ruinian; Xiao, Yangjian
Abstract : Analyses of catastrophic collapse of some adjacent precast concrete box beam bridges reveal the fact that the hinge joints between the adjacent beams were not sufficiently designed. The joint failure caused by deterioration is the result of system reliability deficiency of this type of bridges. To understand the system performance of the bridges, the redundancy and robustness of a bridge model with a scale of 1 ∶ 2, based on the prototype design drawings for 10-meter adjacent box beam bridges in China, were assessed through a system safety evaluation procedure. The result confirmed the assumption that the redundancy and robustness of certain adjacent precast concrete beam bridges did not meet the pertinent requirements proposed in National Cooperative Highway Research Program (NCHRP) reports 406, 458, and 776 as a result of hinge joint failure. To address the current design deficiencies, a system factor is recommended in this paper to calculate the nominal resistance that reflects the level of redundancy of this type of bridges. In addition, a new framework is proposed to address the particular structural feature and topology of adjacent precast concrete beam bridges for the assessment of structural redundancy and robustness, which can reduce the computation complexity compared to existing approaches. The full-range load test performed in this research verified the previous research results on bridge system safety that were mainly based on theoretical analysis and simulations.